VISUAL DESIGN FRAMEWORKS FOR CREATIVE QUALITY MANAGEMENT: INTEGRATING LEAN SIX SIGMA IN CONTEMPORARY DESIGN INDUSTRIES - Gomkale, Shruti; Dorshetwar, Kirti Sanjay; Kumar, Jaideep; Ramchandra, Joshi Rohit; Mardikar, Madhavi; Chopra, PKP Gaitry (ShodhKosh: Journal of Visual and Performing Arts, 2025)
The contemporary design industry operates at the intersection of creativity, visual communication, and quality-driven production, demanding structured yet flexible frameworks to sustain innovation. This study proposes a visual design framework for creative quality management by integrating Lean Six Sigma principles within contemporary design industries. Moving beyond traditional industrial applications, Lean Six Sigma is reinterpreted as a visual and strategic tool to enhance creative workflows, reduce process inefficiencies, and improve design consistency without constraining artistic expression. The framework emphasizes visual thinking, design iteration, and process transparency, aligning quality management practices with creative decision-making. Through conceptual analysis and illustrative design-process models, the study demonstrates how visual mapping, workflow optimization, and feedback loops can support design quality across disciplines such as graphic design, media production, fashion, and digital arts. The proposed framework bridges the gap between creativity and systematic quality management, offering designers and creative managers a structured approach to maintain artistic integrity while achieving operational excellence. This research contributes to the growing discourse on interdisciplinary design management by positioning Lean Six Sigma as a design-enabled methodology rather than a purely industrial tool, thereby expanding its relevance within visual and creative industries.